The AUN/SEED-Net Joint Regional Conference in Transportation, Energy, and Mechanical Manufacturing Engineering Proceeding of RCTEMME2021, Hanoi, Vietnam - Le, Anh-Tuan.; Pham, Van-Sang.; Le, Minh-Quy.; Pham, Hoang-Luong.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book (The AUN/SEED-Net Joint Regional Conference in Transportation, Energy, and Mechanical Manufacturing Engineering) gathers selected papers submitted to the 14th Regional Conference in Energy Engineering and the 13th Regional Conference in Mechanical Manufacturing Engineering in the fields related to intelligent equipment, automotive engineering, mechanical systems and sustainable manufacturing, renewable energy, heat and mass transfer. Under the theme of (3z(BIntegration and Innovation for Sustainable Development,(3y (BThis book consists of papers in the aforementioned fields presented by researchers and scientists from universities, research institutes, and industry showcasing their latest findings and discussions with an emphasis on innovations and developments in embracing the new norm, resulting from the COVID-19 pandemic.s
Evaluation of factors influencing the freezing time of the Pangasius fillets -- Oscillation measurement of the magnetic compass needle employing deep learning technique -- Vehicle crash analysis and airbag simulation in HyperWorks.
Keywords: Industrial engineering; Production engineering; Transportation engineering; Traffic engineering; Materials; Catalysis; Force and energy; Green chemistry; Sustainability; Sustainable architecture; Industrial and Production Engineering; Transportation Technology and Traffic Engineering; Materials for Energy and Catalysis; Green Chemistry; Sustainability; Sustainable Architecture/Green Buildings; Engineering -- Congresses